DETERMINAN TRANSAKSI NONTUNAI DI INDONESIA DENGAN PENDEKATAN ERROR CORRECTION MECHANISM (ECM) MODEL - Zulfa Nur Fajri Ramadhani; Siskarossa Ika Oktora; Indonesian Journal of Statistics and Its Applications IJSA (Indonesian Journal of Statistics and Applications, 2019)
Consumption is an activity that must be done by everyone. In order to consume something, a transaction is needed to get the goods or services desired. One kind of transaction that is used by many people nowadays is non-cash transaction. Since Bank Indonesia established Gerakan Nasional Non Tunai (GNNT) in August 2014, the value of non-cash transactions exceeds the value of cash transactions. It happenned because people prefer non-cash to cash transaction which is easier, safer, more practical, and more economical. Besides, an increase in non-cash transactions can also be influenced by other factors. Therefore, a study is conducted to analyze the determinants of non-cash transactions from the macro side by using Error Correction Mechanism (ECM). The data used in this study are secondary data from Bank Indonesia and Badan Pusat Statistik with monthly period from January 2010 until December 2017. The results showed that in the long run, private savings and BI rate have positive effect on non-cash transactions. In the short run, private savings and money supply have positive effect on non-cash transactions. While inflation does not affect non-cash transactions, both in the short and long run.